The Evolution of the Identity of Islamic Architecture After Prophet Muhammad (pbuh): Some Observations - Spahic, Omer (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Evolution of the Identity of Islamic Architecture After Prophet Muhammad (pbuh): Some Observations